Sentinel Node Navigation Surgery Using Indocyanine Green in Patients with Lung Cancer - Ito, Norimasa; Fukuta, Mikihisa; Tokushima, Takeshi; Nakai, Kaoru; Ohgi, Shigetsugu (Surgery today (Tokyo, Japan), 2004)
To investigate the potential use of sentinel node navigation surgery (SNNS) using indocyanine green (ICG) in lung cancer. The subjects were 38 patients with stage cN0 lung cancer. After thoracotomy, we injected 5 ml ICG and 400 U hyaluronidase around the tumor, and identified the stained lymph nodes (LNs) intraoperatively by inspection. Postoperatively, we measured ICG concentrations in the dissected LNs. Lymph nodes with an ICG concentration of more than 1.5 times the mean were defined as sentinel nodes (SNs). There were 30 pN0, 6 pN1, and 2 pN2 cancers. The tumor size ranged from 11 to 75 (mean 31 +/- 15) mm. Sentinel nodes were identified by inspection in 7 (18.4%) of the 38 patients. Lymphatic mapping with ICG concentration was successful in 38 (100%) of 38. One SN was found in 18 patients and two SNs were found in 20. The SN predicted the status of metastasis of all LNs in 37 (97%) of 38. Metastases were identified in the SN alone in 5 (62.5%) of 8. There was one false negative, caused by a metastatic LN being occupied by tumor cells. These findings support the efficiency of SNNS for clinically node-negative lung cancer.